Pengaruh Penggantian Sikat Gigi Segera Setelah Scaling and Root Planing terhadap Kadar Streptococcus sanguinis Saliva pada Pasien Gingivitis - Muhammad Dzaky Sayyid Effendi; Lino Sefa; Nila Kasuma (Journal of Pharmaceutical and Sciences, 2026)
Gingivitis is an inflammatory condition associated with microbial biofilm accumulation. Scaling and root planing (SRP) is an effective therapy for reducing microbial load; however, bacterial recolonization may occur after treatment. This study aimed to evaluate the effect of toothbrush replacement as an adjunctive home-care intervention after SRP on salivary Streptococcus sanguinis levels in patients with gingivitis. This experimental study used a pretest–posttest intervention design involving 36 gingivitis patients divided into control and intervention groups (18 subjects each). All participants received SRP, while the intervention group received a new toothbrush after SRP. Clinical parameters, including Gingival Index (GI) and Oral Hygiene Index-Simplified (OHI-S), and salivary S. sanguinis levels were evaluated before and after intervention. Saliva samples were analyzed using quantitative real-time polymerase chain reaction (qPCR). Both groups showed significant improvements in GI and OHI-S after SRP (p < 0.001). The mean salivary S. sanguinis level in the control group decreased from 4.94 ± 0.13 to 4.93 ± 0.12 (Δ -0.01; p = 0.863), while the intervention group decreased from 4.83 ± 0.23 to 4.76 ± 0.14 (Δ -0.07; p = 0.367). Post-intervention analysis demonstrated a significantly lower S. sanguinis level in the toothbrush replacement group compared with the control group (4.76 ± 0.14 vs. 4.93 ± 0.12; mean difference = 0.16; 95% CI: 0.07–0.26; p = 0.001). Toothbrush replacement following SRP may provide additional benefits in controlling microbial colonization and supporting periodontal health maintenance in patients with gingivitis.